2021
DOI: 10.1186/s12879-021-05923-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of an outbreak associated with total parenteral nutrition contaminated with NDM-producing Leclercia adecarboxylata

Abstract: Background This study aimed to determine the epidemiological, microbiological, and molecular characteristics of an outbreak of carbapenem-resistant Leclercia adecarboxylata in three hospitals associated with the unintended use of contaminated total parental nutrition (TPN). Methods For 10 days, 25 patients who received intravenous TPN from the same batch of a formula developed sepsis and had blood cultures positive for L. adecarboxylata. Antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Recently, Garza-Gonzalez et al reported an outbreak of carbapenem-resistant L. adecarboxylata associated with the unintended use of contaminated total parental nutrition. All the isolates were carbapenemase producers and positive for bla(NDM-1), bla(TEM-1B) and bla(SHV-12) genes [24]. Choudhary et al also reported the first isolation and characterization of multidrug-resistant Leclercia species from animal clinical case from India [25].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Garza-Gonzalez et al reported an outbreak of carbapenem-resistant L. adecarboxylata associated with the unintended use of contaminated total parental nutrition. All the isolates were carbapenemase producers and positive for bla(NDM-1), bla(TEM-1B) and bla(SHV-12) genes [24]. Choudhary et al also reported the first isolation and characterization of multidrug-resistant Leclercia species from animal clinical case from India [25].…”
Section: Discussionmentioning
confidence: 96%
“…Similar to the bla NDM-4 -harboring IncX3 and IncFIA plasmid carried by E. coli which have been reported in China previously ( 8 , 9 ), pNDM4-191773, an IncFII(Yp)-like plasmid that produced NDM-4, showed the conservative flanking sequence and mobile elements around bla NDM-4 (IS 91-groEL-groES-cutA-dsbD-trpF-ble MBL -bla NDM-4 -Δ IS ba125 ). IncFII(Y)-type plasmids were related to the worldwide spread of bla NDM-1 within K. pneumoniae in South Africa ( 43 ), Leclercia adecarboxylata in Mexico ( 44 ), and bla VIM -carrying K. grimontii in Switzerland ( 45 ). To note, the transfer frequency of pNDM4-191773 was higher at room temperature, indicating that it carries a transmission risk in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reporting resistance determinants in strains from several sources is important to recognize the emergence of multidrug-resistant strains that can be acquired in the hospital environment and in the community and spread to different niches. Since the previous works reporting the emergence of MDR strains of L. adecarboxylata, multidrug resistance in this bacterial species is increasing [13,15,[44][45][46], therefor, surveillance and reporting of such isolates is of clinical importance and may eventually have epidemiological relevance. Conversely, we observed a differential distribution of plasmids among the strains ranging from 7 to 125 kbps in co-occurrence with Plasmid Addiction Systems.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, with a Whole Genome Sequencing approach, our working group recently reported the co-occurrence of resistance genes and virulence genes present in important human pathogens within L. adecarboxylata strains, suggesting the need to consider this species as an emerging pathogen [13]. The clinical relevance of L. adecarboxylata has been demonstrated since the isolation of this microorganism as causative agent in monomicrobial infections such as wound, conjunctive, urinary tract infections (UTI), and bloodstream infections in immunocompetent patients [2, 3, 6–11, 14, 15]. Spiegelhauer et al ., discussed the need for co-infection of L. adecarboxylata due to the poor adherence and invasion capacity to HeP-2 cells, however, they considered important the cytotoxic effect of the bacterium on that cell line [16].…”
Section: Introductionmentioning
confidence: 99%